Clinical investigation of dynamic and enduring aspects of global cognition in aged population. (21st September 2021) - Truong, Quoc C.; Choo, Carol; Numbers, Katya; Merkin, Alexander G.; Brodaty, Henry; Kochan, Nicole A.; Sachdev, Perminder S.; Feigin, Valery. L.; Medvedev, Oleg N.
Abstract: Background: A major issue in evaluating the cognitive status of ageing populations is a clear distinction between enduring and dynamic aspects of global cognition necessary for evaluating risks of dementia and effectiveness of preventive interventions. Materials and methods: Generalizability Theory was applied to investigate dynamic and enduring aspects of global cognition using longitudinal data over 10 years of follow‐up. Measures included the Mini‐Mental Status Examination (MMSE) and the Telephone Interview for Cognitive Status‐modified (TICS‐M). The sample ( N  = 238) included 154 females, mean age = 76.54 years, SD = 3.94 from the Sydney Memory and Ageing Study. Results: The MMSE measured dynamic and enduring aspects of cognition to a comparable degree with 56% of variance explained by enduring aspects and 44% by dynamic aspects and showed low sensitivity/high specificity in detecting dementia. A shortened version of the MMSE (MMSE‐D8) better captured dynamic aspects of cognition after removing three items less sensitive to change. The TICS‐M predominantly measured enduring aspects of cognition (72%) with the remaining 28% due to dynamic aspects and displayed high sensitivity/high specificity for dementia screening. Conclusions: The MMSE measures both dynamic and enduring cognitive aspects and is suitable for general clinical assessments, while the MMSE‐D8 can be used to monitor transitory changes of global cognition over time. The TICS‐M is more useful for measuring enduring features of cognition and screening for dementia. Our findings highlight the value of generalizability theory to distinguish dynamic and enduring features of cognition, which may contribute to preventive interventions and monitoring cognitive ability over time.